Nurse Preceptor Experience in Preceptorship Program: A Systematic Literature Review of Qualitative Studies - Moh Heri Kurniawan; Bahtiar Bahtiar (International Journal of Nursing and Health Services (IJNHS), 2018)
This systematic literature review describes the experiences of the nurse preceptor in the preceptorship program in health care services. Data was collected from three databases: EBSCO, ScienceDirect, and Scopus. Qualitative, peer-reviewed, original studies published in English from 2013 until 2017 and exploring preceptor experiences of the preceptorship program were involved. The manuscripts were selected by screening titles, abstracts and full papers and the quality of the studies was measured. Data were analysed using content analysis.Ten studies were chosen for the review. Nurse preceptor experiences were divided into four main categories: experiences related to the preparation; experiences related to the preceptee; experiences preceptor role during the program; and experiences related to work environment. The findings establish that the nurse preceptor has a great impact to determine the quality of nursing services to the new graduate nurses, but many challenges face during the program.